2020
DOI: 10.3389/fpsyg.2020.587058
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Scaffolding of Social and Intellectual Collaboration in Small Groups: A Comparative Case Study

Abstract: This comparative case study features two small groups of students engaging in collaborative dialog about social issues. Based on social constructivist theories, the two groups were compared across three major components of the small groups system: social dynamics, intellectual collaboration, and teacher scaffolding. Our goal was to holistically analyze these small group processes to understand why some small groups were highly successful while others were not, even within the same intervention and with the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…However, teachers not only engaged in cognitive scaffolding, but also managed group dynamics during the literary dialogues. Kraatz et al (2020) showed the strong interdependence between cognitive depth of interpersonal social reasoning and the affective quality of group dynamics (e.g., high regard for others' perspectives and group members' equal access to the conversational floor). Therefore, effective scaffolding of intellectual depth requires that teachers be attentive to the social group dynamics, wherein students compete by pushing their own arguments, show little respect for other options, and frequently interrupt.…”
Section: Educational Approachesmentioning
confidence: 99%
“…However, teachers not only engaged in cognitive scaffolding, but also managed group dynamics during the literary dialogues. Kraatz et al (2020) showed the strong interdependence between cognitive depth of interpersonal social reasoning and the affective quality of group dynamics (e.g., high regard for others' perspectives and group members' equal access to the conversational floor). Therefore, effective scaffolding of intellectual depth requires that teachers be attentive to the social group dynamics, wherein students compete by pushing their own arguments, show little respect for other options, and frequently interrupt.…”
Section: Educational Approachesmentioning
confidence: 99%
“…The emerging themes of this study contribute to the growing understanding of scaffolding strategies in the flipped practice course in undergraduate nursing education. Although many studies equated scaffolding with any support given by the teacher, the key characteristics of scaffolding, which were defined as contingency, fading and transfer of responsibility, have received more emphasis in the research [ 15 17 ]. Two common threads of thought are raised to prompt further discussion.…”
Section: Discussionmentioning
confidence: 99%
“…There are few documented studies that seek to comprehend students’ subjective experiences with the support strategy utilized by teachers in FC. Scaffolding is a concept used in education to describe the temporary assistance given to students to help them with problem solving [ 15 ]. Three common principles are highlighted in previous scaffolding literature, which are known as contingency, fading, and transfer of responsibility [ 16 ].…”
Section: Introductionmentioning
confidence: 99%